2018
DOI: 10.1155/2018/3502401
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-nonenal Alkylated and Peroxynitrite Nitrated Proteins Localize to the Fused Mitochondria in Malpighian Epithelial Cells of Type IV CollagenDrosophilaMutants

Abstract: Background. Human type IV collagenopathy is associated with mutations within the COL4A1 and to a less extent the COL4A2 genes. The proteins encoded by these genes form heterotrimers and are the highest molar ratio components of the ubiquitous basement membrane. The clinical manifestations of the COL4A1/A2 mutations are systemic affecting many tissues and organs among these kidneys. In order to uncover the cellular and biochemical alterations associated with aberrant type IV collagen, we have explored the pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Photomicrographs of the common oviducts were generated by confocal laser scanning fluorescence microscopy (Olympus Life Science Europa GmbH, Hamburg, Germany). Microscope configurations were set up as described [29]. Briefly, objective lens: UPLSAPO 60x (water, NA: 0.90); sampling speed: 8 µs/pixel; line averaging: 2x; scanning mode: sequential unidirectional; excitation: 405 nm (DAPI), 543 nm (Texas Red) and 488 nm (Alexa Fluor 488); laser transmissivity: 7% were used for DAPI, 15% for Alexa Fluor 488 and 20% for Texas Red.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photomicrographs of the common oviducts were generated by confocal laser scanning fluorescence microscopy (Olympus Life Science Europa GmbH, Hamburg, Germany). Microscope configurations were set up as described [29]. Briefly, objective lens: UPLSAPO 60x (water, NA: 0.90); sampling speed: 8 µs/pixel; line averaging: 2x; scanning mode: sequential unidirectional; excitation: 405 nm (DAPI), 543 nm (Texas Red) and 488 nm (Alexa Fluor 488); laser transmissivity: 7% were used for DAPI, 15% for Alexa Fluor 488 and 20% for Texas Red.…”
Section: Methodsmentioning
confidence: 99%
“…In these mutants we have demonstrated severe myopathy [9], irregular and thickened BM, detachment of the gut epithelial and visceral muscle cells from the BM [27], intestinal dysfunction, overexpression of antimicrobial peptides, excess synthesis of hydrogen peroxide and peroxynitrite [28]. In epithelial cells of Malpighian tubules we demonstrated fused mitochondria, membrane peroxidation [29], actin stress fibers and irregular integrin expression [30]. Our results indicated that muscular dystrophy may also be present in col4a1 mutant Drosophila [31].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore tested the effects of mechanical load in the col4a1 G552D2 mutant and recorded the development of actin stress fibers and irregular, uneven actin staining in epithelial cells of the Malpighian tubules [27]. In a separate study, we noted mitochondrial fusion and co-localization of peroxynitrite-nitrated and 4-hydroxy-2-nonenal alkylated proteins with abnormal mitochondria [28]. Mitochondrial fusion in Malpighian epithelium is pronounced in the col4a1 G552D1 mutant at the restrictive temperature (Figure 3), as a sign of the mutation-induced stress, whereas the level of protein nitration assessed qualitatively remain unchanged in the wild-type control and mutant strains under both the permissive and restrictive conditions (Figure 3).…”
Section: Compromised Excretory System In the Mutantsmentioning
confidence: 99%
“…The genome of the fruit fly consists of a pair of type IV collagen genes, col4a1 and col4a2 in a head-to-head orientation, similar to mammals [24]. The mutant phenotype is systemic, affecting the gut [25,26], the excretory organ Malpighian tubules [27,28] and the muscles manifested in muscular dystrophy [29]. The recessive phenotype of the col4a1 -/homozygotes leads to lethality in the late embryonic to early larval phases at the permissive temperature [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation